Variation in cystectomy pathology reporting practice—results from an international survey of 212 pathologists - Griffin, Jon; Hartmann, Arndt; Comperat, Eva (Virchows Archiv, 2024)
The pathological assessment of cystectomy specimens is important for accurate prognostic information and to inform adjuvant therapy decisions. However, there is limited evidence regarding the best approach to fixation, dissection, block selection and microscopic assessment of cystectomies. We report the results of an international survey of 212 pathologists and their approach to cystectomy pathology. There is variation at all stages of the specimen journey including in fixation and dissection techniques, and in the approach to evaluating residual tumour. This is particularly evident in the post-neoadjuvant chemotherapy setting where there is variable use of response scoring systems and differing approaches to sampling. We also find variation in the use of digital and molecular pathology in cystectomy specimens. Finally, we have suggested areas for future research in cystectomy pathological assessment.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Bladder cancer; Cystectomy; Dissection; Grossing; Neoadjuvant chemotherapy; Pathological response score